Qur'anic Ethics and Educational Praxis: Integrating Al- Fatihah into Islamic Character Development - Sahidin, La; Abidin, Zainal; Muslahuddin, Muslahuddin (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study addresses the need for a spiritually grounded basis for cultivating honesty and trustworthiness in Islamic character education by examining how the tawhidic theology of Surah Al-Fatihah can be translated into an educational framework. The research aims to identify tawhid-based ethical values in QS. Al-Fatihah (1):1–7 and explain their relevance for forming integrity-oriented character outcomes. Employing qualitative library research, the study analyzes the Qur’anic text as primary data and tafsir literature, tawhid studies, and character education scholarship as secondary data, using structured thematic analysis through verse-based coding, categorization of ethical themes, and mapping procedures to connect theological values with character constructs. The analysis yields six core values rububiyyah (divine lordship), rahmah (compassion), eschatological accountability (hisab), ikhlas (sincerity), isti‘anah (reliance on God), and hidayah (divine guidance)—which correspond to four character outcomes: moral responsibility, integrity, spiritual resilience, and ethical orientation. These findings indicate that internalizing tawhidic values strengthens internal self-regulation (muraqabah), empathetic truthfulness, and consistent trustworthiness rooted in divine accountability rather than social conformity. Educationally, the model supports reflective pedagogy, moral habituation through ritual practice, and the cultivation of an integrity-based school culture, positioning Surah Al-Fatihah as a compact ethical curriculum for curriculum design and teacher formation across diverse educational settings.